Versatile Roles of LKB1 Kinase Signaling in Neural Development and Homeostasis - Kuwako, Ken-ichiro; Okano, Hideyuki (Frontiers in Molecular Neuroscience, 2018)
Kinase signaling pathways orchestrate a majority of cellular structures and functions across species. LKB1 (liver kinase B1, also known as STK11 or Par-4) is a ubiquitously expressed master serine/threonine kinase that plays crucial roles in numerous cellular events, such as polarity control, proliferation, differentiation and energy homeostasis, in many types of cells by activating downstream kinases of the AMPK (AMP-activated protein kinase) subfamily members. In contrast to the accumulating evidence for LKB1 functions in nonneuronal tissues, its functions in the nervous system have been relatively less understood until recently. In the brain, LKB1 initially emerged as a principal regulator of axon/dendrite polarity in forebrain neurons. Thereafter, recent investigations have rapidly uncovered diverse and essential functions of LKB1 in the developing and mature nervous system, such as migration, neurite morphogenesis, myelination and the maintenance of neural integrity, demonstrating that LKB1 is also a multifunctional master kinase in the nervous system. In this review, we summarize the expanding knowledge about the functional aspects of LKB1 signaling in neural development and homeostasis.